ANALISIS LOYALITAS PELANGGAN YANG DIPENGARUHI OLEH KUALITAS PRODUK, KEPERCAYAAN DAN KEPUASAN PELANGGAN PADA PT DUNIA ALKES UTAMA DI KOTA TANGERANG - Henny Sumiaty; Tin Agustina; Mohammad Bukhori (Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Dunia Alkes Utama is a retail business in Tangerang City that provides Pharmaceutical products and Medical Devices. The current phenomenon of conventional retail businesses tends to decline because it is eroded by online sales or online marketing which is increasingly widespread. The purpose of this research is to provide and analyze: 1) the influence of product quality on customer loyalty, 2) the influence of consumer trust on customer loyalty, and 3) the influence of satisfaction on customer loyalty. This research applies quantitative research method. This research was taken from who are already customers of PT Dunia Alkes Utama in the city of Tangerang. The population used in this study are customers who have bought and visited PT Dunia Alkes Utama with a sample of 100 respondents bay way of taking purposive sampling technique. The results provided explanation is: 1) PT Dunia Alkes Utama product quality had a positive effect on customer loyalty at PT Dunia Alkes Utama 2) PT Dunia Alkes Utama customer trust had a positive effect on customer loyalty at PT Dunia Alkes Utama 3) PT Dunia Alkes Utama customer satisfaction had a positive effect on customer loyalty PT Dunia Alkes Utama.